Characterization of Tea Made from Mangrove Leaves Sonneratia alba: - Lompoh, Aisyah; Husain, Rahim; Manteu, Shindy Hamidah (Sam Ratulangi University, 2025)
Tea processing techniques are carried out through drying. The drying process is necessary to obtain tea products with a long shelf life. Temperature and time are important parameters in the drying process that can affect the physical (yield) and chemical (antioxidant activity, total phenolic content, moisture content, and ash content) characteristics of tea products during drying. This study aims to characterize tea made from mangrove leaves (Sonneratia alba) using sun drying and oven drying treatments. The methods used in this study were organoleptic tests for hedonic quality (color, taste, aroma), yield, moisture content, and phytochemicals in mangrove leaf tea. The results showed that the drying process significantly affected the yield, moisture content, and organoleptic properties. The organoleptic properties of the tea were as follows: color 5.48–8.44, aroma 6.04–7, taste 5.16–6.12. The oven-dried yield was 2.5%, and the sun-dried yield was 2.66%. The moisture content of oven-dried tea was 9.93% and sun-dried tea was 18.98%. Phytochemicals in oven-dried and sun-dried tea were positively detected as alkaloids, flavonoids, saponins, tannins, terpenoids, and polyphenols. Keywords: phytochemicals; yield; moisture content; mangrove tea; functional food Abstrak Teknik pengolahan teh dilakukan dengan cara pengeringan. Proses pengeringan diperlukan untuk mendapatkan produk teh yang memiliki masa simpan yang panjang. Suhu dan waktu merupakan parameter penting pada proses pengeringan yang dapat mempengaruhi karakteristik fisik (rendemen) dan kimia (aktivitas antioksidan, total fenolik, kadar air dan kadar abu) produk teh selama pengeringan. Penelitian ini bertujuan untuk karakterisasi teh berbahan baku daun mangrove (Sonneratia alba) dengan pelakuan pengeringan sinar matahari dan pengeringan oven. Metode yang digunakan dalam penelitian ini yaitu uji organoleptik mutu hedonik (warna, rasa, aroma), rendemen, kadar air dan fitokimia pada teh daun mangrove. Hasil penelitian menunjukkan bahwa perbedaan proses pengeringan memberikan pengaruh nyata terhadap nilai rendeman, kadar air dan organoleptik. Nilai organoleptik teh yaitu warna 5,48 - 8,44, aroma 6,04-7, rasa 5,16 - 6,12. Rendemen kering oven 2,5 % dan kering matahari 2,66%. Nilai kadar air teh kering oven 9,93% dan teh kering matahari 18,98&. Fitokimia pada teh kering oven dan matahari positif terdeteksi adanya senyawa alkaloid, flavonoid, Saponin, tanin, terpenoid, dan polifenol. Kata Kunci: fitokimia; rendemen; kadar air; teh mangrove; pangan fungsional.